Structure and chemical composition of mixed benzylguanine- and methoxy-terminated self-assembled monolayers for immobilization of biomolecules - Bruns, Michael; Barth, Christoph; Howell, Caitlin; Kölsch, Patrick (Surface and interface analysis, 2012)
Covalent immobilization of biomolecules has become a subject of great interest in recent years because of the expected diversity of applications, for example, biosensors in diagnosis, lab-on-chip technology, and modern cell culture focused on cell adhesion, migration, and differentiation. Our approach is to produce self-assembled monolayers (SAMs) on gold surfaces based on mixtures of a benzylguanine-terminated thiol and a thiol, carrying ethylene glycol groups. The benzylguanine head group of such SAMs acts as a substrate for the SNAP-tag system allowing for covalent attachment of any protein of interest fused to this tag. For this purpose, it is essential to determine the orientation and chemical composition of these layers. In this study, we use the strength of combining complementary surface analytical methods to achieve a comprehensive characterization. The chemical composition and the covalent binding of the thiols were proved by X-ray photoelectron spectroscopy (XPS). The orientation of the SAMs together with thickness information was achieved by nondestructive depth profiles reconstructed from parallel angle-resolved XPS data and energy-resolved photoelectron emission spectroscopy (PES). High-sensitivity low-energy ion scattering and sum-frequency-generation spectroscopy corroborate the XPS/PES results. Copyright © 2012 John Wiley & Sons, Ltd.
Gesehen am 11.09.2018